2020
DOI: 10.1016/j.omtm.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Gene Therapy Treats Bone Complications of Mucopolysaccharidosis Type II Mouse Models through Bone Remodeling Reactivation

Abstract: Mucopolysaccharidosis type II is a disease caused by organ accumulation of glycosaminoglycans due to iduronate 2-sulfatase deficiency. This study investigated the pathophysiology of the bone complications associated with mucopolysaccharidosis II and the effect of lentivirus-mediated gene therapy of hematopoietic stem cells on bone lesions of mucopolysaccharidosis type II mouse models in comparison with enzyme replacement therapy. Bone volume, density, strength, and trabecular number were significantly higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 58 publications
(72 reference statements)
1
22
0
Order By: Relevance
“…Another method to achieve high levels of IDS is through ex vivo genetic modification of HSC. Transplantation of lentiviral transduced HSC resulted in an increase in serum IDS levels several-fold higher than wild type [167,236]. GAG accumulation in all tested tissues, including the brain, was resolved.…”
Section: Treatment In Animalsmentioning
confidence: 90%
See 1 more Smart Citation
“…Another method to achieve high levels of IDS is through ex vivo genetic modification of HSC. Transplantation of lentiviral transduced HSC resulted in an increase in serum IDS levels several-fold higher than wild type [167,236]. GAG accumulation in all tested tissues, including the brain, was resolved.…”
Section: Treatment In Animalsmentioning
confidence: 90%
“…Moreover, bone manifestations were affected with significant reduction of zygomatic arch width. In-depth analysis of bone parameters revealed higher osteoclast number, suggesting activation of bone resorption [236].…”
Section: Treatment In Animalsmentioning
confidence: 95%
“…Among various serotypes of adeno‐associated virus (AAV), AAV9 has been selected as the vector due to its brain tropism (Fu et al., 2018; Hinderer et al., 2016; Laoharawee et al., 2017; Motas et al., 2016). In addition to the AAV study, lentiviral vector‐mediated animal studies have been reported (Gleitz et al., 2018; Wada et al., 2020). As the novel mode of delivery, nanoparticle‐mediated administration of the IDS enzyme and gene has also been reported (Rigon et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An active IDS enzyme requires a biotransformation of cysteine to formylglycine for maximal catalytic activity (Demydchuk et al., 2017). To achieve this, the SUMF1 enzyme plays a key role (Gleitz et al., 2018; Wada et al., 2020). In the case of the IDS enzyme, a previous study reported that 68.1%–79.4% of cysteine in therapeutic enzyme preparation from mammalian cell culture systems has been converted into formylglycine (Chung et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of retroviruses is their integration into the host genome, the risk of mutagenesis and immunogenicity. However, research using other viral vectors on model organisms was continued and showed promising results [ 46 , 47 , 48 ]. Further clinical trials are conducted using various forms of gene therapy, including genome editing systems such as zinc finger nucleases (ZFNs) or Clustered Regularly Interspaced Short Palindromic Repeat/Cas9 (CRISPR/Cas9) [ 48 ].…”
Section: Gene Therapymentioning
confidence: 99%